Possibilities of using virtual educational technologies in the formation of natural science (SIENS) skills of elementary school students. - DJurayeva Nargiza Narkulovna (Genius Journals, 2023)
The article notes that one of the topical issues is the further improvement of the methods of using virtual educational technologies for the formation of natural science (SIENS) skills of primary school students today. Methods for solving this problem, designing and implementing virtual educational technologies in the educational process, taking into account individual educational characteristics in the design of virtual educational technologies, and the possibility of using virtual educational technologies will be highlighted
Keywords: Natural; sciences; methods and methods; technology